The development of a standardized skill assessment for junior volleyball players - Gabbett, T. J.; Georgieff, B. (International Journal of Sports Physiology and Performance, 2006)
To develop a skill assessment for junior volleyball players and to evaluate the reliability, validity, and sensitivity of the test for detecting training-induced improvements in skill. Methods: Thirty junior volleyball players (mean ± SD age, 15.5 ± 1.0 years) participated in this study. Subjects performed tests of spiking, setting, serving, and passing skills on 2 separate occasions to determine test-retest reliability of accuracy. Two expert coaches evaluated the players` technique and reevaluated it 1 month after the initial evaluation to determine the intratester reliability for technique measurements. A third expert coach determined the intertester reliability for technique measurements. The validity of the test to discriminate players of different playing abilities was evaluated by testing junior national, state, and novice volleyball players. Finally, each player participated in an 8-week skill-based training program. Results: Accuracy measurements and intratester and intertester ratings of players` technique proved to be highly reproducible (intraclass correlation coefficient, r, .85 to .98, range of typical error of measurement 0.2% to 10.0%). A progressive improvement in skill was observed with increases in playing level, while training-induced improvements were present in all skill tasks. Conclusions: These results demonstrate that skill-based testing offers a reliable method of quantifying development and progress in junior volleyball players. In addition, the skill-testing battery was useful in successfully discriminating playing ability among junior volleyball players of varying levels, and it was sensitive to changes in skill with training. These findings demonstrate that skill-based testing is useful for monitoring the development of junior volleyball players.